AI and empathy: the possibility of reciprocal human-robot empathic interaction (HRI) – some experiences from socially assistive robots (SARs) in elderly care - Petrovič, Tanja (Monitor ISH, 2021)
Empathy is a vital part of human relationships. It remains a challenging concept with inconsistent measurement tools, yet widely accepted as an important factor for interpersonal interactions in healthcare. With robot development novel types of relationship emerge. The key question is whether there is a possibility of the existence of empathic Human-Robot Interaction (HRI), as a reciprocal quality of human empathy vs. artificial empathy. Furthermore, we aim to discover its specificities, with regard to a substantial eeriness in this domain. Socially Assistive Robots (SARs), designed for Aged-Care Settings, face an increased usage due to a pressing need for care for the elderly in a modern society. Because we as humans tend to regularly establish relationships and anthropomorphise objects, among them also robots, a wide range of challenges arise. Discussing empathy in HRI requires a shift in human perspective, as only scarce traces of the concept are detected. While a key perspective on empathy is caring for the other person, empathy in HRI does have a conceptual potential. The paper challenges the anthropocentric attempt to define empathic and ethical benchmark for HRI, with a request to exclude our own negative personal and societal aspects from programing an algorithm, when dealing with human vulnerability and rights.
Keywords: Interakcija med človekom in robotom; Oskrba starostnikov; roboti; umetna inteligenca